Posttraumatic subclavian artery pseudoaneurysm: An endovascular approach - Ilayakumar Paramasivam; Shabnam Fathima; N Sritharan; Krishna Muralidharan; Jayanth Vijaykumar (Indian Journal of Vascular and Endovascular Surgery, 2020)
The use of minimally invasive vascular techniques for vascular injuries is on the rise. We report a case of stab injury with pseudoaneurysm of the subclavian artery treated with “covered” stent of the subclavian artery. The patient presented a month after the injury and was hemodynamically stable. Hence, a computed tomography angiogram of the arch of the aorta and left upper limb was performed and taken up for elective stenting of the left subclavian artery. The completion angiogram showed complete exclusion of the pseudoaneurysm, with normal runoff to the upper extremity. In conclusion, penetrating arterial trauma in inaccessible sites can be successfully managed with minimal morbidity by endovascular means.